A Zonal‐Meridional Projection Method for Quantifying Global Land‐Ocean Moisture Transport - Chong Zhang; Guohe Huang; Chenglong Zhang (International Journal of Climatology, 2026)
Accurate quantification of moisture transport between the ocean and the land is essential for understanding the global water and energy cycles. Existing methods based on flux divergence or trajectory analysis are computationally demanding and not well suited to irregular coastlines. Here we develop a zonal‐meridional projection (ZMP) method that directly measures water‐moisture fluxes across global coastal interfaces. Vertically integrated moisture fluxes derived from ERA5 reanalysis (0.25°, 1979–2020) are projected onto coastal‐normal directions and multiplied by a signed land‐side boundary length derived from sub‐segmented grid edges. This line‐integral formulation preserves the physical consistency of the flux direction and automatically distinguishes inflow and outflow through the signs of wind and coastline orientation. It also improves computational efficiency by avoiding conditional checks of wind direction or coastal type. The results reveal coherent ocean‐to‐land inflow corridors along monsoonal and intertropical regions and a statistically significant upward trend in total inflow since 1979, consistent with an intensifying global hydrological cycle. The proposed ZMP method provides a geometrically precise, scalable and computationally efficient approach for quantifying land‐ocean moisture exchange in both reanalysis and climate‐model applications.